Pemahaman Konsep Kerajaan Israel dan Yehuda Dalam Perspektif Historis: Analisis Terhadap Sumber-sumber Tertulis dan Arkeologis - Bahri, Fajar; Fitriani (Yayasan Salam Cerdas Al-Fattah, 2023)
This research aims to deepen the understanding of the concept of the Kingdom of Israel and Judah from a historical perspective through analysis of written sources, especially the Book of Samuel and the Book of Kings, as well as archaeological finds, both structural and artifacts. The main research question involves evaluating the consistency between written sources and archaeological finds, as well as how information from both can provide better insight into the general history of the region. The research method applied is an in-depth literature study which includes analysis of classical texts and tracing of recent archaeological finds. The results of the study report a significant correlation between the stories in the Book of Samuel and the Book of Kings and archaeological finds, indicating a strong relevance to general historical understanding of the period. The implication is that these findings can enrich the historical narrative reconstruction of the Kingdoms of Israel and Judah and provide new insights into the social and political dynamics of the past. The conclusions of this research provide a strong argument in support of a deeper understanding of the concept of the Kingdoms of Israel and Judah, while highlighting the importance of integrating written sources and archaeological findings in historical research.